Dihydrotestosterone regulation of cyclooxygenase-2 expression in bovine endometrial epithelium cells by androgen receptor mediated EGFR/PI3K/Akt pathway. Issue 214 (November 2021) - Xiao, Longfei; Sun, Wanxu; Su, Yue; Lu, Ning; He, Yanan; Sheng, Xihui; Qi, Xiaolong; Xing, Kai; Guo, Yong; Chang, Di; Wang, Xiangguo; Zhao, Junjin; et al.
Highlights: DHT levels increased in the late pregnancy phase in bovine endometria. DHT showed a dose-dependent increased COX-2 expression and PGF2α release in EECs. DHT via AR mediated EGFR/PI3K/ Akt/NFkB pathway regulated COX-2 expression. Abstract: Uterine prostaglandins F2α (PGF2α) is essential for implantation, initiation of luteolysis and delivery. Previous studies have demonstrated that the expression of Cyclooxygenase-2 (COX-2), an enzyme limiting PGF2α rate, is regulated by steroid hormones, and also dihydrotestosterone (DHT) may be involved in regulating COX-2 expression both positively and negatively. However, it remains unclear how whether DHT regulates COX-2 expression and consequent PGF2α release in bovine endometrial epithelial cells (EECs). In this study, we evaluated the localization of the two isoforms of DHT synthetase 5α-reductase (5α-red1 and 5α-red2) and androgen receptor (AR) in bovine endometria by immunohistochemistry, and investigated 5α-red1, 5α-red2, AR, and DHT levels at the different stages of endometria (follicle, early-, mid-, and late-pregnancy phases). The results showed that 5α-red1, 5α-red2 and AR all were expressed in endometria, and their expressions and the level of DHT significantly increased in the late-pregnancy phase compared with the mid-pregnancy phase. Moreover, we cultured EECs from the mid-pregnancy phase and the in vitro study showed that DHT dose-dependently increased COX-2 expression and PGF2a release, but AR antagonist (flutamide) inhibited the stimulating effect via DHT. In addition, the DHT-induced COX-2 expression and PGF2α release were subjected to the regulation of both EGFR/PI3K/Akt/NFkB signaling as the inhibitors of EGFR (AG1478) and PI3K/Akt (LY294002) and NFkB (QNZ) attenuated the DHT mediated effect. Taken together, the results demonstrated that DHT-induced COX-2 expression and consequent PGF2α release in bovine EECs were mediated through AR-derived EGFR transactivation and PI3K/Akt cascade leading to NFkB activation.